(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Nephrotic syndrome (NS) is distinguished by heavy proteinuria (urine protein:creatinine ratio ?2000 mg/g or ?300 mg/dL, or 3+ protein on urine dipstick), hypoalbuminemia (?2.5 g/dL), and edema. Leakage of massive amounts of serum proteins into the urine leads to a hypercoagulable state, a higher rate of infectious disease, and the dysregulation of fluid balance. Idiopathic nephrotic syndrome (INS) is one of the most common renal problems in children encountered in day-to-day nephrology practices. The present study was aimed to evaluate the oxidant/ antioxidant status by measuring paraoxonase (PON) activities as well as total antioxidant capacity in steroid sensitive nephrotic syndrome (frequent and infrequent relapse) and compares it with healthy control children . Paraoxonase activity by spectrophotometer in three groups consisted of age and sex matched (30) patients with Frequent relapse nephrotic syndrome FRNS , (30) patients with infrequent relapse nephrotic syndrome (IFRNS) and (30) healthy control children. The serum level of paraoxonase activity in infrequent relapse group was 101.61±43.0 IU which far less than frequent relapse group (160.44±44.22 IU) or controls (228.35±32.35 IU) with highly significant differences. Of note, the difference between control group and frequent relapse group was highly significant.